Lithium metal negative electrode and electrochemical device including the same
A lithium metal negative electrode with a cracked oxide layer addresses dendrite growth and non-uniform deposition issues, enhancing desorption and extending battery life by promoting uniform electrodeposition and reducing resistance.
Patent Information
- Application Number
- JP2024535295
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-01-12
- Filing Date
- 2023-01-12
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-01-12
AI Technical Summary
Lithium metal secondary batteries face issues such as dendrite growth, side reactions with electrolytes, and decreased charging/discharging efficiency due to the formation of non-uniform oxide layers on the lithium metal surface, leading to battery instability and reduced lifespan.
A lithium metal negative electrode with a surface oxide layer featuring cracked portions and non-cracked portions, formed through heat treatment, to enhance lithium desorption and suppress dendrite growth.
The cracked oxide layer improves lithium desorption, enables uniform electrodeposition, and extends the battery's lifespan by preventing dendrite growth and reducing resistance.
Smart Images

Figure 2024546135000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a lithium metal negative electrode and an electrochemical device including the same.
[0002] This application claims priority to Korean Patent Application No. 10-2022-0004911, filed on January 12, 2022, the entire contents of which are incorporated herein by reference in their entirety in the specification and drawings. [Background technology]
[0003] Recently, as interest in energy storage technology has increased, the fields of application have expanded to include mobile phones, tablet PCs, laptop computers, and camcorders, as well as the energy of electric vehicles (EVs) and hybrid electric vehicles (HEVs), and research and development of electrochemical devices has been gradually increasing. Electrochemical devices are the field that has attracted the most attention in this regard, and recently, the development of such batteries has led to research and development on new electrode and battery designs in order to improve capacity density and specific energy.
[0004] Among these electrochemical elements, lithium metal secondary batteries that use lithium metal as the negative electrode, such as lithium-sulfur batteries (Li-S batteries), have a theoretical capacity of 3,862mAh / g, which is very high, and are attracting attention as the next generation of high capacity batteries using light lithium metal as the negative electrode active material. In lithium-sulfur batteries, a reduction reaction of sulfur and an oxidation reaction of lithium metal occur during discharge, and at this time, sulfur is converted into the ring-shaped S 8 The lithium polysulfide (LiPS) is formed from the lithium ions, and the lithium-sulfur battery is a battery in which the polysulfide is completely LiPS. 2 It is characterized by showing a stepwise discharge voltage until it is reduced to S.
[0005] However, lithium metal secondary batteries, such as lithium-sulfur batteries, experience a decrease in charge / discharge efficiency during the charge / discharge process due to side reactions of the electrolyte (accumulation of by-products due to the decomposition of the electrolyte) and instability of lithium metal (dendrites growing on the lithium metal anode, causing a short circuit), resulting in a deterioration of the battery's lifespan.
[0006] In particular, lithium metal, which is an anode active material, is prone to forming large-area dendrites and reacts with salts and additives in the electrolyte to form a solid electrolyte interphase (SEI), which continuously consumes the salts and additives in the electrolyte and ultimately accelerates battery degradation.
[0007] Therefore, in order to use lithium metal as the negative electrode, it is necessary to develop technology that suppresses the growth of dendrites and prevents the consumption of salts and additives in the electrolyte. Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention aims to provide a lithium metal negative electrode in which an oxide layer having cracks is formed on the surface, thereby improving lithium desorption, enabling uniform electrodeposition, and suppressing dendrite growth, and an electrochemical element including the same.
[0009] Another object of the present invention is to provide a method for producing a lithium metal negative electrode in which an oxide layer having cracks is formed on the surface, thereby improving lithium desorption, enabling uniform electrodeposition, and suppressing dendrite growth. [Means for solving the problem]
[0010] In order to achieve the above object, according to one aspect of the present invention, there is provided a lithium metal negative electrode according to the following embodiment.
[0011] According to a first embodiment, there is provided a lithium metal anode comprising a lithium metal layer and an oxide layer located on at least one surface of the lithium metal layer, the oxide layer having a cracked portion and a non-cracked portion.
[0012] According to a second embodiment, in the first embodiment, the oxide layer having the cracked portion may have a cracked portion and a non-cracked portion, and an area ratio of the cracked portion to the non-cracked portion may be 2:8 to 9:1.
[0013] According to a third embodiment, in the first or second embodiment, the thickness of the oxide layer having the crack portion may be 50% or less based on the maximum thickness of the oxide layer.
[0014] According to a fourth embodiment, in any one of the first to third embodiments, the oxide layer having the crack portion may have a thickness of 10 nm to 10 μm.
[0015] According to a fifth embodiment, in any one of the first to fourth embodiments, the lithium metal layer may have a thickness of 1 μm to 200 μm.
[0016] According to a sixth embodiment, there is provided a method for manufacturing a lithium metal negative electrode including a lithium metal layer and an oxide layer formed on at least one surface of the lithium metal layer, the method for manufacturing a lithium metal negative electrode according to any one of the first to fourth embodiments including a step of forming a crack portion in the oxide layer.
[0017] According to a seventh embodiment, in the sixth embodiment, the step of forming the crack portion may include a step of heat treating the lithium metal negative electrode under a vacuum atmosphere at a pressure of 0.001 to 1 Torr.
[0018] According to an eighth embodiment, in the sixth or seventh embodiment, the step of forming the crack portion may include a step of heat treating the lithium metal negative electrode in an inert atmosphere.
[0019] According to a ninth embodiment, in any one of the sixth to eighth embodiments, the step of forming the crack portion may include a step of heat treating the lithium metal negative electrode at 40°C to 120°C.
[0020] According to a tenth embodiment, in any one of the sixth to ninth embodiments, the step of forming the crack portion may include a step of heat treating the lithium metal negative electrode at 65°C to 85°C.
[0021] According to an eleventh embodiment, there is provided an electrochemical device including the lithium metal negative electrode of any one of the first to fifth embodiments.
[0022] According to a twelfth embodiment, in the eleventh embodiment, the electrochemical device may include a lithium secondary battery.
[0023] According to a thirteenth embodiment, in the twelfth embodiment, the lithium secondary battery may include a lithium ion battery, a lithium sulfur battery, a lithium-lithium symmetric cell, or two or more thereof. Effect of the Invention
[0024] In the lithium metal negative electrode according to one embodiment of the present invention, cracks are formed in the oxide layer on the surface of the lithium metal, which improves lithium desorption, and the increased surface area of the lithium metal allows for uniform electrodeposition and inhibits the growth of dendrites.
[0025] An electrochemical device including a lithium metal negative electrode according to an embodiment of the present invention has an improved life span by including a lithium metal negative electrode having an oxide layer with cracks on its surface.
[0026] The following drawings attached to this specification illustrate preferred embodiments of the present invention and, together with the detailed description of the invention, serve to further understand the technical ideas of the present invention. Therefore, the present invention should not be interpreted as being limited to only the matters described in the drawings. [Brief description of the drawings]
[0027] [Figure 1] 1 is a SEM photograph of the surface of the lithium metal negative electrode produced in Example 1-3. [Diagram 2] 1 is a SEM photograph of the surface of the lithium metal negative electrode produced in Comparative Example 1-1. [Diagram 3] FIG. 2 is a graph showing the cycle life performance of the lithium-lithium symmetric cell prepared in Example 2-1. [Figure 4] FIG. 2 is a graph showing the cycle life performance of the lithium-lithium symmetric cell prepared in Example 2-2. [Diagram 5] FIG. 13 is a graph showing the cycle life performance of the lithium-lithium symmetric cell prepared in Example 2-3. [Figure 6] FIG. 13 is a graph showing the cycle life performance of the lithium-lithium symmetric cell prepared in Example 2-4. [Figure 7] FIG. 13 is a graph showing the cycle life performance of the lithium-lithium symmetric cell prepared in Example 2-5. [Figure 8] FIG. 13 is a graph showing the cycle life performance of the lithium-lithium symmetric cell prepared in Comparative Example 2-1. [Figure 9] FIG. 1 is a graph showing the cycle life performance of the lithium-sulfur batteries produced in Examples 3-1 to 3-5 and Comparative Example 3-1. [Figure 10] 1 is a cross-sectional view of a lithium metal negative electrode according to an embodiment of the present invention. [Figure 11] 1 is a cross-sectional view of a lithium metal negative electrode according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0028] Hereinafter, a preferred embodiment of the present invention will be described in detail with reference to the attached drawings. Prior to this, the terms and words used in the specification and claims should not be interpreted as being limited to their ordinary or dictionary meanings, but should be interpreted as having meanings and concepts according to the technical ideas of the present invention, in accordance with the principle that the inventor himself can appropriately define the concepts of terms in order to best describe the invention.
[0029] Therefore, it should be understood that the embodiments described in this specification and the configurations shown in the drawings are merely the most preferred embodiment of the present invention and do not represent the entire technical idea of the present invention, and that there may be various equivalents and modifications that can be substituted for them at the time of this application.
[0030] When lithium metal is exposed to the atmosphere, it can be dissolved in water depending on the type of gas present in the atmosphere. 2 CO 3 , Li 2 Oxide layers such as O, LiOH, etc. are formed on the surface of lithium metal. These oxide layers not only make the current density on the surface of lithium metal non-uniform and reduce the surface area required for lithium dissolution and deposition, but also act as a resistive layer and reduce ionic conductivity. Another problem is that the oxide layers cause lithium to be deposited non-uniformly.
[0031] The morphology of the deposited lithium is related to the charge / discharge current density, the type of electrolyte, and the growth of lithium in the form of dendrites, moss, or spheres. Some of the lithium growing in the form of dendrites breaks off during discharge to form dead lithium, which is not capable of electrochemical charging and discharging but has strong chemical reactivity. When lithium metal is used as the negative electrode due to the formation of such dead lithium, it becomes difficult to reversibly charge and discharge it. As a result, the electrode life characteristics of lithium metal are poor even in non-aqueous electrolytes, and its thermal stability is also poor.
[0032] The present inventors have found that the above-mentioned problems can be solved by forming cracks in the oxide layer present on the surface of metallic lithium, and have completed the present invention.
[0033] A lithium metal negative electrode according to one aspect of the present invention includes a lithium metal layer and an oxide layer located on at least one surface of the lithium metal layer, the oxide layer having a cracked portion and a non-cracked portion.
[0034] The lithium metal may be lithium or a lithium alloy. In this case, the lithium alloy may include an element capable of being alloyed with lithium. Specifically, the lithium alloy may be an alloy of lithium and one or more elements selected from the group consisting of Si, Sn, C, Pt, Ir, Ni, Cu, Ti, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Sb, Pb, In, Zn, Ba, Ra, Ge, and Al.
[0035] The lithium metal negative electrode may further include a current collector on one side of the lithium metal layer. The current collector may be a negative electrode current collector. The negative electrode current collector is not particularly limited as long as it does not induce a chemical change in the battery and has high conductivity. For example, it may be selected from the group consisting of copper, aluminum, stainless steel, zinc, titanium, silver, palladium, nickel, iron, chromium, alloys thereof, and combinations thereof. The stainless steel may be surface-treated with carbon, nickel, titanium, or silver, and the alloy may be an aluminum-cadmium alloy. In addition, baked carbon, a non-conductive polymer or a conductive polymer surface-treated with a conductive material, etc. may be used. Typically, a copper foil plate is used as the negative electrode current collector.
[0036] In addition, the negative electrode current collector may be in various forms, such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc., with or without fine irregularities on the surface. In addition, the negative electrode current collector may have a thickness in the range of 3 to 500 μm. When the thickness of the negative electrode current collector satisfies the above range, the current collecting effect can be ensured, and also, when the cell is folded and assembled, the processability can be easily ensured.
[0037] The lithium metal layer may be in the form of a sheet or foil, and in some cases, may be in the form of lithium or a lithium alloy deposited or coated on a current collector by a dry process, or particulate lithium or a lithium alloy deposited or coated on a current collector by a wet process.
[0038] Lithium metal may form a thick oxide layer on the surface of the lithium metal when it is exposed to oxygen or reacts with the lubricant components during rolling of the lithium metal anode.
[0039] A lithium metal anode according to one aspect of the present invention includes a lithium metal layer and an oxide layer located on at least one surface of the lithium metal layer, the oxide layer having a cracked portion and a non-cracked portion.
[0040] In this specification, the "cracked portion" of the oxide layer may refer to a region where the oxide layer is thinner than the adjacent "non-cracked portion" of the oxide layer. For example, the "non-cracked portion" may refer to a region where the oxide layer is thicker, and the "cracked portion" may refer to a region where the oxide layer is thinner than the adjacent "non-cracked portion". Specifically, the "cracked portion" may refer to a region of the oxide layer of the "non-cracked portion", i.e., the thickness of the lithium metal oxide layer, which is 50% or less, 40% or less, 30% or less, 20% or less, or 10% or less based on the maximum thickness. Alternatively, the "cracked portion" may refer to a region where the lithium metal layer is exposed due to the absence of the oxide layer.
[0041] FIG. 10 is a cross-sectional view of a lithium metal negative electrode according to an embodiment of the present invention, and FIG. 11 is a cross-sectional view showing a lithium metal negative electrode according to an embodiment of the present invention in more detail.
[0042] 10 and 11, an oxide layer 20 is located on one surface of a lithium metal layer 10, and the oxide layer 20 has a cracked portion 30 and a non-cracked portion 40. The cracked portion 30 may be a portion of the lithium metal oxide layer that is 50% or less of the maximum thickness. The cracked portion 30 may refer to a region where the lithium metal layer 10 is exposed due to the absence of an oxide layer. Meanwhile, since it is impossible for the surface of the oxide layer to be completely flat, a portion of the oxide layer surface having a minute height difference does not need to be considered as a cracked portion. For example, the non-cracked portion 50 is lower in height than the thickest portion of the oxide layer, but is distinguished from the cracked portion 30.
[0043] 10 and 11 show cross sections of a lithium metal negative electrode according to an embodiment of the present invention, the lithium metal negative electrode according to the present invention is not limited to the structures shown in Fig. 10 and 11. For example, although Fig. 10 and Fig. 11 show a case where an oxide layer is located on one side of a lithium metal layer, oxide layers may be located on both sides of a lithium metal layer according to other embodiments of the present invention.
[0044] In this specification, the term "crack portion" may include a recess, a hole, an opening, a trench pit, etc. formed on the surface of an oxide layer. The depth of the crack portion may refer to the difference in height perpendicular to the surface of the lithium metal from the highest height of the oxide layer formed on the surface of the lithium metal to the lowest point of the crack portion. For example, if the highest thickness of the oxide layer formed on the surface of the lithium metal is 100 nm and the thickness of the oxide layer remaining in the crack portion is 5 nm, the depth of the crack portion may be 95 nm.
[0045] In addition, since it is impossible for the surface of the oxide layer to be completely flat, the cracks do not necessarily mean the portions having minute height differences on the surface of the oxide layer, i.e., the cracks may only mean the portions having a depth of at least 20 nm or 30 nm.
[0046] The depth of the crack may be 60% or more, 70% or more, 80% or more, or 90% or more of the thickness of the oxide layer. Also, the oxide layer may be completely removed and not exist at the crack, in which case the depth of the club may be 100% of the thickness of the oxide layer.
[0047] In the present specification, the term "cracked portion" may refer to an area where no oxide is present in an image observed with a scanning electron microscope (SEM) at 30,000 magnifications. Alternatively, the term "cracked portion" may refer to an area shown in black or a darker color than the adjacent "non-cracked portion" in an image observed with a scanning electron microscope (SEM) at 30,000 magnifications. Meanwhile, the "non-cracked portion" may be shown in white or a lighter color than the adjacent cracked portion. In this case, the scanning electron microscope (SEM) photographing may be performed immediately after heat treatment, immediately after battery formation, or immediately before battery cycling, but is not limited thereto. In addition, the SEM observation is performed by observing the surface of the lithium metal negative electrode from above, and is performed in a vertical direction (top-down) of a plane parallel to the oxide layer and lithium metal. The "cracked area" and "non-cracked area" can be determined by visually observing the SEM image and judging areas that are black or relatively darker than adjacent areas as cracked areas, and areas that are white or relatively lighter than adjacent areas as non-cracked areas.
[0048] The cracked and non-cracked parts can be more accurately distinguished by converting the image observed by SEM into a binary image. Specifically, the image observed by SEM can be converted into a binary image divided into white and black, so that the cracked and non-cracked parts can be clearly distinguished.
[0049] For example, a raw image observed by a SEM may be converted to a binary image by thresholding, which may be global thresholding, Otsu thresholding, or adaptive thresholding.
[0050] The global thresholding process is a process in which a threshold is determined, and then pixel values exceeding the threshold are colored black, and pixel values not exceeding the threshold are colored white.
[0051] The Otsu binarization is to create a binary image using the Otsu algorithm. When converting to a binary image, the Otsu algorithm arbitrarily determines a threshold value to divide pixels into two categories, and repeats the process of finding the brightness distribution of the two categories. After that, the threshold value that gives the most uniform brightness distribution of the two categories is selected from all possible cases. The Otsu algorithm has the advantage that the optimal threshold value is automatically found.
[0052] The adaptive thresholding process divides an image into a number of regions and calculates a threshold value for converting the image into a binary image using only the pixel values around the regions. When the original image has a variety of background colors or hues, it is difficult to create a vivid binary image using a single threshold value. However, by using the adaptive thresholding process, a binary image of excellent quality can be created.
[0053] In one embodiment of the present invention, the area ratio of the cracked portion to the non-cracked portion can be calculated using an image of the surface of the oxide layer observed by SEM. For example, after the cracked portion and the non-cracked portion are separated by the above-mentioned method, a boundary line between the cracked portion and the non-cracked portion can be set, and the areas of the cracked portion and the non-cracked portion can be derived to calculate the area ratio between the cracked portion and the non-cracked portion. In this case, the boundary line between the cracked portion and the non-cracked portion can be set as a boundary line that reliably separates the white or bright portion from the black or dark portion in the SEM image. On the other hand, even within the non-cracked region, which is the oxidized layer, there are very bright and slightly bright areas in the non-cracked portion due to minute height differences in the oxidized layer, but the cracked portion as defined in this invention means a portion that is less than a certain percentage of the thickness of the oxidized layer in the non-cracked portion. Therefore, even if very bright and slightly bright areas are observed in the non-cracked portion, this is a difference that occurs due to minute height differences in the non-cracked portion, so the slightly bright areas are also considered to be non-cracked portions and are not considered to be cracked portions as they are relatively less bright.
[0054] In one embodiment of the present invention, the non-cracked portion may form one or more "oxide islands" that are non-cracked portions surrounded by the cracked portions. In this case, the oxide island (non-cracked portion) may refer to a region having a thickness equal to or greater than the maximum oxide layer thickness in the region surrounded by the cracked portion, or a thickness of 90% or more, 80% or more, 70% or more, 60% or more, or 50% or more. For example, the "oxide island" may be an oxide layer region (non-cracked portion) having a thickness of 100 to 120 nm, surrounded by an oxide region (cracked portion) having a thickness of 5 nm or less.
[0055] In one embodiment of the present invention, the "oxide island" (i.e., non-cracked) region may appear white or lighter than the adjacent cracked regions in an image observed with a scanning electron microscope (SEM) at 30,000 magnification. Meanwhile, the region (i.e., cracked region) that is lacking in oxide surrounding the "oxide island" may appear black or darker than the adjacent non-cracked regions. In this case, the SEM observation may be performed immediately after the heat treatment of the lithium metal negative electrode, immediately after the battery is manufactured, or immediately before cycling the battery, but is not limited thereto. In addition, the SEM observation is performed by observing the surface of the lithium metal negative electrode from above, that is, in a vertical direction (top-down) of a plane parallel to the oxide layer and lithium metal.
[0056] In one embodiment of the present invention, the oxide layer can be a lithium oxide layer. Alternatively, the oxide layer can be a natural oxide layer. A natural oxide layer is formed on the metal surface by a reaction between the metal and atmospheric components. A natural oxide layer of lithium is usually formed in a bilayer structure. In the bilayer structure, the inner layer is lithium oxide (Li 2 O), and the outer layer is made up of lithium hydroxide (LiOH) and lithium carbonate (Li 2 CO 3 Lithium metal can also react with nitrogen to form lithium nitride (Li 3 N), and thus the native oxide layer of lithium may include lithium nitride. However, the constituent materials of the lithium oxide layer are not limited to the above materials and may be composed of various materials that can be applied by a person skilled in the art.
[0057] In the lithium metal anode according to an embodiment of the present invention, the oxide layer formed on the surface of the lithium metal may be entirely or partially removed or destroyed due to the presence of cracks in the oxide layer formed on the surface of the lithium metal. The cracks may remove or destroy the entire or partial thick oxide layer acting as a resistance to lithium desorption, thereby exposing the lithium metal, or may thin the oxide layer, thereby reducing the overvoltage required for lithium desorption, thereby improving lithium desorption. In the electrodeposition process, the cracks may be used as nucleation sites for lithium, and as the surface area of the lithium metal increases due to the cracks, the surface electric field is reduced, suppressing dendrite growth, thereby making the electrodeposition uniform.
[0058] In one embodiment of the present invention, the oxide layer may have a cracked portion and a non-cracked portion, and the area ratio of the cracked portion to the non-cracked portion may be 2:8 to 9:1, or 4:6 to 6:4. When the area ratio of the cracked portion to the non-cracked portion satisfies the above-mentioned range, improvement of lithium desorption, uniform electrodeposition, and suppression of dendrite growth are more easily achieved, thereby improving the battery life. The areas of the cracked portion and the non-cracked portion may be calculated from an image of the oxide layer observed by a scanning electron microscope (SEM).
[0059] In one embodiment of the present invention, at least a part or all of the cracks have an elongated shape, and the average width of the cracks may be 1 to 500 nm, 10 to 400 nm, or 50 to 300 nm.
[0060] In one embodiment of the invention, at least some or all of the cracks have an elongated shape, and the average length of the cracks may be 2.5 μm or more, or 3 μm or more.
[0061] In one embodiment of the present invention, the vertical cross section of the crack has at least a part or all of an elongated shape, and the ratio of the average width to the average length of the crack can be 0.001 to 0.2, 0.01 to 0.2, or 0.03 to 0.2.
[0062] In this specification, "elongated shape" should be understood broadly as a non-spherical shape, i.e. a shape having different diameters in different perpendicular directions, such as an elliptical shape, and is not limited to an elliptical shape, but may also include irregular shapes such as rectangular, serpentine, etc.
[0063] The length of the crack is the distance between the two furthest points of the crack, and can be determined from an image of lithium metal on which an oxide layer is formed, observed with a scanning electron microscope (SEM). Specifically, it can be determined from an image of the crack observed on the surface when the surface of the electrode is observed with the SEM.
[0064] The width of the crack means the distance between the oxide layers on one side and the other side of the crack in a direction perpendicular to an imaginary line connecting the two furthest points of the crack, and can be determined from an image of lithium metal on which an oxide layer is formed, taken with a scanning electron microscope (SEM). Specifically, it can be determined from an image of the surface of the electrode observed with the SEM. Specifically, it can be determined from an image of the crack observed on the surface when the surface of the electrode is observed with the SEM.
[0065] In one embodiment of the present invention, the total thickness of the oxide layer may be 10 nm to 10 μm, or 20 nm to 1 μm. That is, for example, the thickness of the non-cracked portion of the oxide layer may be within the above range. When the thickness of the oxide layer is within the above range, it is possible to easily prevent deterioration during storage of lithium metal, and it is possible to more easily prevent the problem of lithium not being released due to high resistance.
[0066] In one embodiment of the present invention, the lithium metal layer may be in the form of a sheet, foil or thin film. The lithium metal layer may have a thickness of 1 to 200 μm, or 5 to 100 μm. When the lithium metal layer has a thickness within the above range, it provides a sufficient lithium source for battery operation and makes it easier to realize a high energy density.
[0067] The lithium metal negative electrode according to an embodiment of the present invention may be prepared by the following method, but is not limited thereto.
[0068] According to one aspect of the present invention, a method for manufacturing a lithium metal anode including a lithium metal layer and an oxide layer formed on at least one surface of the lithium metal layer includes forming cracks in the oxide layer.
[0069] In the lithium metal anode according to an embodiment of the present invention, a crack may be formed in an oxide layer formed on the surface of the lithium metal by heat-treating the lithium metal. As the volume of the lithium metal expands during the heat treatment of the lithium metal, a crack may be formed in the oxide layer present on the surface of the lithium metal.
[0070] In one embodiment of the present invention, the lithium metal may be heat-treated at 40° C. to 120° C., 60° C. to 100° C., or 65° C. to 85° C. to form cracks in the oxide layer formed on the surface of the lithium metal. When the temperature conditions for heat-treating the lithium metal satisfy the above conditions, cracks are sufficiently formed in the oxide layer on the surface of the lithium metal, and the lithium evaporates, reducing the thickness of the lithium metal and reducing the lithium negative electrode active material, which can more effectively prevent the problem, and thus the life of an electrochemical device including the same can be further improved.
[0071] In one embodiment of the present invention, the lithium metal may be heat-treated under a vacuum atmosphere at a pressure of 0.001 to 1 Torr to form cracks in the oxide layer formed on the surface of the lithium metal. By heat-treating the lithium metal under the above pressure conditions and in a vacuum atmosphere, it is possible to more easily prevent residual gas from reacting with the surface of the lithium metal to further form an oxide layer. In addition, it is possible to more easily prevent cracks from occurring during the heat treatment process and the lithium metal exposed by the cracks from immediately reacting with residual gas to re-form an oxide layer.
[0072] In another embodiment of the present invention, the lithium metal may be heat-treated under an inert atmosphere to form cracks in the oxide layer formed on the surface of the lithium metal. Here, the inert gas forming the inert atmosphere means a gas that does not cause a chemical reaction, such as argon or nitrogen, but is not limited to the above gas and includes all gases that a general engineer can use. By heat-treating the lithium metal under an inert atmosphere, it is possible to more easily prevent residual gas from reacting with the surface of the lithium metal to further form an oxide layer. In addition, it is possible to more easily prevent cracks from occurring during the heat treatment process and the lithium exposed at the cracks or the thinned oxide layer from immediately reacting with residual gas to further form an oxide layer.
[0073] In one embodiment of the present invention, the lithium metal may be heat-treated at 40° C. to 120° C. or 60° C. to 100° C. under a vacuum atmosphere of 0.001 to 1 Torr pressure to form cracks in the oxide layer formed on the surface of the lithium metal.
[0074] In another embodiment of the present invention, the lithium metal may be heat-treated at 40° C. to 120° C., or 60° C. to 100° C. in an inert atmosphere to form cracks in the oxide layer formed on the surface of the lithium metal.
[0075] The electrochemical device according to one embodiment of the present invention has a lithium metal negative electrode having an oxide layer with cracks on its surface, thereby improving the life span.
[0076] The electrochemical device of the present invention includes all devices that perform electrochemical reactions, and specifically includes all kinds of primary batteries, secondary batteries, fuel cells, solar cells, and capacitors such as supercapacitor devices.
[0077] In one embodiment of the present invention, the electrochemical device may be any lithium secondary battery commonly used in the art that uses lithium metal as a negative electrode, including a lithium ion battery, a lithium sulfur battery, or a lithium-lithium symmetric cell.
[0078] According to an embodiment of the present invention, an electrochemical device includes a positive electrode, a lithium metal negative electrode, a separator, and a non-aqueous electrolyte. The electrochemical device may be manufactured by disposing a positive electrode and a negative electrode facing each other, interposing a separator therebetween, and then injecting the non-aqueous electrolyte.
[0079] Hereinafter, the positive electrode, the separator, and the non-aqueous electrolyte in the electrochemical device according to an embodiment of the present invention will be described in more detail.
[0080] The positive electrode includes a positive electrode active material, a binder, and a conductive material. The positive electrode active material may be applicable to a general electrochemical device. For example, the positive electrode active material may include a lithium nickel cobalt manganese compound (lithium NCM compound). In addition, elemental sulfur (S 8 ), a sulfur-based compound, or a mixture thereof. The sulfur-based compound may specifically include Li 2 S n (n ≥ 1), organic sulfur compounds or carbon-sulfur complexes ((C 2 S x ) n(x=2.5-50, n≧2). The positive electrode active material may include a sulfur-carbon composite. Since the sulfur material alone does not have electrical conductivity, it may be used in combination with a conductive material. The carbon material (or carbon source) constituting the sulfur-carbon composite may be any one commonly used in the art as long as it has a porous structure or a high specific surface area. For example, the porous carbon material may be, but is not limited to, graphite; graphene; carbon black such as denka black, acetylene black, ketjen black, channel black, furnace black, lamp black, or thermal black; carbon nanotubes (CNTs) such as single-walled carbon nanotubes (SWCNTs) or multi-walled carbon nanotubes (MWCNTs); carbon fibers such as graphite nanofibers (GNFs), carbon nanofibers (CNFs), or activated carbon fibers (ACFs); activated carbon; or two or more of these materials. The shape of the porous carbon material may be spherical, rod-like, needle-like, plate-like, tubular, or bulk-like, and is not particularly limited as long as it is applicable to an electrochemical device.
[0081] In addition, the carbon material has pores, and the porosity of the pores may be 40 to 90%, or 60 to 80%. When the porosity of the pores is within the above-mentioned range, lithium ions are easily transferred normally, and the problem of a decrease in mechanical strength can be more easily prevented. The pore size of the carbon material may be 10 nm to 5 μm, or 50 nm to 5 μm. When the pore size of the carbon material is within the above-mentioned range, lithium ions can easily pass through, and battery short circuit and safety problems due to contact between electrodes can be more easily prevented.
[0082] The binder is a component that aids in binding between the positive electrode active material and the conductive material and between the positive electrode active material and the current collector. Examples of the binder include, but are not limited to, polyvinylidene fluoride (PVdF), polyvinylidene fluoride-polyhexafluoropropylene copolymer (PVdF / HFP), polyvinyl acetate, polyvinyl alcohol, polyvinyl ether, polyethylene, polyethylene oxide, alkylated polyethylene oxide, polypropylene, polymethyl (meth)acrylate, polyethyl (meth)acrylate, polytetrafluoroethylene (PTFE), polyvinyl chloride, polyacrylonitrile, polyvinylpyridine, polyvinylpyrrolidone, styrene-butadiene rubber, acrylonitrile-butadiene rubber, ethylene-propylene-diene monomer (EPDM) rubber, sulfonated EPDM rubber, styrene-butylene rubber, fluororubber, carboxymethylcellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, or two or more of these.
[0083] The binder may be added in an amount of 1 to 50 parts by weight, or 3 to 15 parts by weight, based on 100 parts by weight of the total weight of the positive electrode. When the content of the binder satisfies the above-mentioned range, it is easy to ensure the adhesive force between the positive electrode active material and the current collector, and it is easy to ensure the battery capacity.
[0084] The conductive material contained in the positive electrode is not particularly limited as long as it does not induce side reactions in the internal environment of the electrochemical device, does not induce chemical changes in the battery, and has excellent electrical conductivity. Representatively, graphite or conductive carbon may be used. For example, graphite such as natural graphite and artificial graphite; carbon black such as carbon black, acetylene black, ketjen black, denka black, thermal black, channel black, furnace black, and lamp black; carbon-based materials having a graphene or graphite crystal structure; conductive fibers such as carbon fibers and metal fibers; carbon fluoride; metal powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives; or two or more of these may be used, but are not necessarily limited thereto.
[0085] The conductive material may be added in an amount of 0.5 to 50 parts by weight, or 1 to 30 parts by weight, based on 100 parts by weight of the total weight of the positive electrode. When the content of the conductive material is within the above-mentioned range, it is easy to improve electrical conductivity, it is easy to prevent deterioration of electrochemical properties, and it is easy to ensure the capacity and energy density of the positive electrode.
[0086] The method of incorporating a conductive material into the positive electrode is not particularly limited, and any method known in the art, such as coating the positive electrode active material, may be used. In addition, if necessary, a conductive second coating layer may be added to the positive electrode active material to replace the addition of the conductive material.
[0087] In addition, a filler may be selectively added to the positive electrode of the present invention as a component for suppressing the expansion of the positive electrode. Such a filler is not particularly limited as long as it does not induce chemical changes in the battery and can suppress the expansion of the electrode. For example, olefin polymers such as polyethylene and polypropylene; fibrous materials such as glass fiber and carbon fiber; etc. may be used.
[0088] The positive electrode may be manufactured by dispersing and mixing the positive electrode active material, binder, conductive material, etc. in a dispersion medium (solvent) to prepare a slurry, applying the slurry onto a positive electrode current collector, and then drying and rolling the slurry. The dispersion medium may be, but is not limited to, N-methyl-2-pyrrolidone (NMP), dimethyl formamide (DMF), dimethyl sulfoxide (DMSO), ethanol, isopropanol, water, or a mixture thereof.
[0089] The positive electrode current collector may be made of platinum (Pt), gold (Au), palladium (Pd), iridium (Ir), silver (Ag), ruthenium (Ru), nickel (Ni), stainless steel (STS), aluminum (Al), molybdenum (Mo), chromium (Cr), carbon (C), titanium (Ti), tungsten (W), ITO (In doped SnO 2 ), FTO (F doped SnO 2 ) and alloys thereof, aluminum (Al) or stainless steel surface-treated with carbon (C), nickel (Ni), titanium (Ti) or silver (Ag), etc., may be used, but are not necessarily limited to these. The positive electrode current collector may be in the form of a foil, film, sheet, punched, porous, foam, etc.
[0090] A conventional separator may be interposed between the positive electrode and the negative electrode. The separator may be a physical separator having a function of physically separating the electrodes and used as a conventional separator, and may be used without any particular limitation. In particular, the separator is preferably one having low resistance to ion movement of the electrolyte and excellent electrolyte impregnation ability. The separator separates or insulates the positive electrode and the negative electrode from each other and allows lithium ions to be transported between the positive electrode and the negative electrode. Such a separator may be porous and made of a non-conductive or insulating material. The separator may be an independent member such as a film, or a coating layer added to the positive electrode and / or the negative electrode.
[0091] Examples of polyolefin-based porous membranes that can be used as the separation membrane include membranes formed from polyolefin-based polymers such as polyethylene (e.g., high density polyethylene, linear low density polyethylene, low density polyethylene, and ultra-high molecular weight polyethylene), polypropylene, polybutylene, and polypentene, either alone or in combination. Examples of nonwoven fabrics that can be used as the separator include nonwoven fabrics made of polymers such as polyphenylene oxide, polyimide, polyamide, polycarbonate, polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate, polyphenylene sulfide, polyacetal, polyethersulfone, polyether ether ketone, and polyester, either alone or in combination. Such nonwoven fabrics are in the form of fibers forming a porous web, and may include spunbond or meltblown fabrics made of tension fibers.
[0092] The thickness of the separator is not particularly limited, but may be 1 to 100 μm, or 5 to 50 μm. When the thickness of the separator is within the above range, the mechanical properties can be maintained, and the problem of the separator acting as a resistance layer, which may cause a decrease in battery performance, can be easily prevented. The pore size and porosity of the separator are not particularly limited, but the pore size may be 0.1 to 50 μm, and the porosity may be 10 to 95%. When the pore size of the separator is within the above range, the separator can be easily prevented from acting as a resistance layer, and the mechanical properties of the separator can be easily maintained.
[0093] The nonaqueous electrolyte may include a first solvent including a heterocyclic compound having one or more double bonds or no double bonds and including at least one oxygen atom and at least one sulfur atom; a second solvent including at least one of an ether-based compound, an ester-based compound, an amide-based compound, and a carbonate-based compound; a lithium salt; and lithium nitrate.
[0094] Hereinafter, the first solvent, the second solvent, the lithium salt, and the lithium nitrate contained in the nonaqueous electrolyte according to one embodiment of the present invention will be described in detail.
[0095] First Solvent The first solvent includes a heterocyclic compound containing at least one double bond or at least one of oxygen and sulfur atoms, and has a characteristic of being difficult to dissolve salt due to delocalization of lone pair electrons of the heteroatom (oxygen atom or sulfur atom). Therefore, a polymer protective film (solid electrolyte interphase; SEI layer) is formed on the surface of lithium metal through a ring opening reaction of the heterocyclic compound in the initial discharge stage of the battery, thereby suppressing the generation of lithium dendrites. Furthermore, decomposition of the electrolyte on the surface of lithium metal and the resulting side reactions are reduced, thereby improving the life characteristics of the electrochemical device.
[0096] That is, the heterocyclic compound of the present invention may contain one or more double bonds in order to form a polymer protective film on the surface of lithium metal, and must contain one or more heteroatoms (oxygen atoms or sulfur atoms) in order to exert effects such as imparting polarity and increasing affinity with other solvents in the electrolyte.
[0097] The heterocyclic compound may be a heterocyclic compound having a 3- to 15-membered ring, a 3- to 7-membered ring, or a 5- to 6-membered ring. In addition, such a heterocyclic compound may be an alkyl group having 1 to 4 carbon atoms, a cyclic alkyl group having 3 to 8 carbon atoms, an aryl group having 6 to 10 carbon atoms, a halogen group, a nitro group (-NO 2 ), amine group (-NH 2 ) and sulfonyl groups (-SO 2 The heterocyclic compound may be a polycyclic compound of a heterocyclic compound and one or more of a cyclic alkyl group having 3 to 8 carbon atoms and an aryl group having 6 to 10 carbon atoms.
[0098] When the heterocyclic compound is substituted with an alkyl group having 1 to 4 carbon atoms, the radicals are stabilized, and side reactions with the electrolyte can be suppressed. When the heterocyclic compound is substituted with a halogen group or a nitro group, a functional protective film can be formed on the surface of lithium metal, and the formed functional protective film can be stable as a compact protective film. In addition, uniform deposition of lithium metal can be achieved. In particular, when the electrochemical device is a lithium-sulfur battery, side reactions between polysulfide and lithium metal can be suppressed.
[0099] Specific examples of the heterocyclic compound include 1,3-dioxolane, 4,5-diethyl-1,3-dioxolane, 4,5-dimethyl-1,3-dioxolane, 4-methyl-1,3-dioxolane, 4-ethyl-1,3-dioxolane, and 1,3-dioxane. ane, 1,4-dioxane, 4-methyl-1,3-dioxane, 2-methyl-1,3-dioxane, furan, 2-methylfuran, 3-methylfuran, 2-ethylfuran, 2-propylfuran, 2-butylfuran, 2,3-dimethylfuran Examples of thiophene include 2,3-dimethylfuran, 2,4-dimethylfuran, 2,5-dimethylfuran, pyran, 2-methylpyran, 3-methylpyran, 4-methylpyran, benzofuran, 2-(2-nitrovinyl)furan, thiophene, 2-methylthiophene, 2-ethylthiophene, 2-propylthiophene, 2-butylthiophene, 2,3-dimethylthiophene, 2,4-dimethylthiophene, and 2,5-dimethylthiophene.
[0100] The first solvent containing such a heterocyclic compound may be included in a volume ratio of 5 to 50 with respect to a volume ratio of 100 of the total organic solvent (i.e., first solvent + second solvent) included in the nonaqueous electrolyte according to one embodiment of the present invention (the remainder being the second solvent). When the content of the first solvent satisfies the above-mentioned range, it is possible to easily prevent a problem in which a protective film is not completely formed on the surface of lithium metal, and it is possible to easily prevent a problem in which the capacity and life of a battery are reduced due to an increase in the surface resistance of the electrolyte and lithium metal.
[0101] In particular, when the positive electrode active material is sulfur, the ability to reduce the amount of polysulfide eluted decreases, making it difficult to suppress an increase in the resistance of the electrolyte, which can be easily prevented.
[0102] Second Solvent The second solvent may include at least one of an ether-based compound, an ester-based compound, an amide-based compound, and a carbonate-based compound, and may dissolve a lithium salt to allow the electrolyte to have lithium ion conductivity, and may also dissolve a positive electrode active material to facilitate an electrochemical reaction with lithium. In particular, when the positive electrode active material is sulfur, the second solvent may dissolve the positive electrode active material sulfur to facilitate an electrochemical reaction with lithium.
[0103] The carbonate compound may be a linear carbonate compound or a cyclic carbonate compound.
[0104] Specific examples of the ether-based compound include, but are not limited to, dimethyl ether, diethyl ether, dipropyl ether, methyl ethyl ether, methyl propyl ether, ethyl propyl ether, dimethoxyethane, diethoxyethane, methoxyethoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol methyl ethyl ether, triethylene glycol dimethyl ether, triethylene glycol diethyl ether, triethylene glycol methyl ethyl ether, tetraethylene glycol dimethyl ether, tetraethylene glycol diethyl ether, tetraethylene glycol methyl ethyl ether, polyethylene glycol dimethyl ether, polyethylene glycol diethyl ether, polyethylene glycol methyl ethyl ether, or two or more thereof.
[0105] Examples of the ester compound include, but are not limited to, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone, ε-caprolactone, or two or more of these.
[0106] The amide-based compound may be a conventional amide-based compound used in the art.
[0107] Examples of the linear carbonate compound include, but are not limited to, dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), ethylmethyl carbonate (EMC), methylpropyl carbonate (MPC), ethylpropyl carbonate (EPC), or two or more of these.
[0108] Examples of the cyclic carbonate-based compound include, but are not limited to, ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, vinylene carbonate, vinylethylene carbonate, halides thereof (such as fluoroethylene carbonate (FEC)), or two or more of these.
[0109] The second solvent may be included in a volume ratio of 50 to 95 with respect to a volume ratio of 100 of the total organic solvent (i.e., the first solvent + the second solvent) included in the nonaqueous electrolyte according to an embodiment of the present invention. When the content of the second solvent satisfies the above-mentioned range, the lithium salt can be sufficiently dissolved, and the problem of poor lithium ion conductivity can be easily prevented, and the problem of the positive electrode active material being precipitated in excess of its dissolving concentration can be easily prevented. In particular, when the positive electrode active material is sulfur, the problem of the positive electrode active material sulfur being precipitated in excess of its dissolving concentration can be easily prevented, and the problem of the shuttle phenomenon between lithium polysulfide and lithium metal negative electrode being aggravated due to excessive sulfur elution, resulting in a shortened lifespan, can be easily prevented.
[0110] Meanwhile, the organic solvent including the first solvent and the second solvent may be included in an amount of 60 to 99.5 wt%, 60 to 99 wt%, 60 to 98 wt%, or 60 to 95 wt%, based on the total weight of the nonaqueous electrolyte according to an embodiment of the present invention. When the organic content is within the above-mentioned range, the problem of the electrolyte increasing in viscosity and decreasing in ionic conductivity, or the problem of the lithium salt or additives not being completely dissolved in the electrolyte, can be easily prevented, and the problem of the lithium salt concentration in the electrolyte decreasing and decreasing in ionic conductivity can be easily prevented.
[0111] Lithium salts The lithium salt is an electrolyte salt used to increase ionic conductivity, and examples of such salts include LiCl, LiBr, LiI, and LiClO. 4 , LiBF 4 , LiB 10 Cl 10 , LiPF 6 , LiCF 3 SO 3 , LiCF 3 CO 2 , LiC 4 BO 8 , LiAsF 6 , LiSbF 6 , LiAlCl 4 , C.H. 3 SO 3 Li, C.F. 3 SO 3 Li, (C 2 F 5 SO 2 ) 2 NLi, (SO 2 F) 2 NLi (i.e., LiFSI), (CF 3 SO 2 ) 2 NLi (i.e., LiTFSI), (CF 3 SO 2 ) 3 Examples of the lithium borane include CLi, lithium chloroborane, lithium aliphatic carboxylate having 4 or less carbon atoms, lithium 4-phenylborate, lithium imide, or two or more of these.
[0112] The lithium salt concentration can be determined in consideration of ion conductivity, and may be, for example, 0.2 to 2 M or 0.5 to 1 M. When the lithium salt concentration satisfies the above-mentioned range, ion conductivity suitable for battery operation can be easily ensured, and an increase in the viscosity of the electrolyte, which leads to a decrease in the mobility of lithium ions, or an increase in the decomposition reaction of the lithium salt itself can be prevented.
[0113] Lithium nitrate According to one embodiment of the present invention, the non-aqueous electrolyte is lithium nitrate (LiNO 3 Lithium nitrate reacts with the lithium metal anode to produce lithium nitride (Li3 By forming a lithium affinity protective film such as lithium oxynitride (LiON) on the surface of the lithium metal anode, the growth of lithium dendrites can be suppressed and the decomposition of the electrolyte components can be prevented, thereby improving the battery life and efficiency.
[0114] If necessary, lanthanum nitrate (La(NO 3 ) 3 ), potassium nitrate (KNO 3 ), Cesium nitrate (CsNO 3 ), magnesium nitrate (Mg(NO 3 ) 2 ), barium nitrate (Ba(NO 3 ) 2 ), lithium nitrite (LiNO 2 ), potassium nitrite (KNO 2 ), Cesium nitrite (CsNO 2 ), or two or more of these.
[0115] The lithium nitrate may be included in an amount of 0.1 to 7 wt%, 0.5 to 5 wt%, or 0.5 to 1.5 wt%, based on 100 wt% of the total weight of the nonaqueous electrolyte. When the lithium nitrate content is within the above range, the problem of a sudden drop in coulombic efficiency can be easily prevented, and the phenomenon of an increase in the viscosity of the electrolyte can be easily prevented.
[0116] The non-aqueous electrolyte according to one embodiment of the present invention includes a first solvent, 1,3-dioxolane, a second solvent, dimethoxyethane, and a lithium salt (CF 3 SO 2 ) 2 The non-aqueous electrolyte may include lithium polysulfide, lithium nitrate, and lithium nitrate. The 1,3-dioxolane and dimethoxyethane have high lithium polysulfide solubility and can stabilize the lithium metal negative electrode. Therefore, when the non-aqueous electrolyte includes the above-mentioned materials, it is possible to show optimal electrochemical device characteristics.
[0117] Meanwhile, the lithium secondary battery according to an embodiment of the present invention can be applied to a battery cell used as a power source for a small device, and can be particularly suitably used as a unit battery of a battery module that is a power source for a medium- to large-sized device. In this respect, the present invention provides a battery module including two or more electrochemical devices electrically connected (series or parallel). The number of electrochemical devices included in the battery module can be variously adjusted in consideration of the use and capacity of the battery module. Furthermore, the present invention provides a battery pack in which the battery modules are electrically connected according to a conventional technique in the art. The battery module and the battery pack can be used as a power source for one or more medium- to large-sized devices including, but not limited to, a power tool; an electric vehicle (EV), an electric vehicle (HEV), and an electric plug-in hybrid electric vehicle (PHEV); an electric truck; an electric commercial vehicle; or a power storage system.
[0118] The present invention will be described in detail below with reference to examples to aid in understanding the present invention. However, the embodiments according to the present invention can be modified in various ways, and the scope of the present invention is not limited to the following examples. The examples of the present invention are provided to more completely explain the present invention to those with average knowledge in the art.
[0119] Example 1-1 A lithium metal film having a thickness of 35 μm was heat-treated in a convection oven at a temperature of 40° C. for 4 hours under a vacuum atmosphere of 0.01 Torr pressure, and then rolled on one side onto a copper current collector to prepare a lithium metal negative electrode.
[0120] Example 1-2 A lithium metal anode was prepared in the same manner as in Example 1-1, except that the heat treatment was performed at a temperature of 60°C.
[0121] Examples 1-3 A lithium metal anode was prepared in the same manner as in Example 1-1, except that the heat treatment was performed at a temperature of 80°C.
[0122] Examples 1-4 A lithium metal anode was prepared in the same manner as in Example 1-1, except that the heat treatment was performed at a temperature of 100°C.
[0123] Examples 1-5 A lithium metal anode was prepared in the same manner as in Example 1-1, except that the heat treatment was performed at a temperature of 120°C.
[0124] Comparative Example 1-1 The 35 μm thick lithium metal was used as the lithium metal anode without any treatment.
[0125] Examples 2-1 to 2-5 and Comparative Example 2-1: Fabrication of Lithium-Lithium Symmetric Cell First, 1% by weight of lithium nitrate based on the total weight of the electrolyte was added to an organic solvent in which 1,3-dioxolane (first solvent) and dimethoxyethane (second solvent) were mixed in a 1:1 volume ratio (v / v), and the electrolyte was cooled to 100°C (CF 3 SO 2 ) 2 NLi(LiTFSI) (lithium salt) was dissolved to a concentration of 1M to prepare a non-aqueous electrolyte.
[0126] The lithium metal negative electrodes prepared in Examples 1-1 to 1-5 and Comparative Example 1-1 were used as the positive and negative electrodes, with the lithium facing each other. Then, a 16 μm-thick porous polyethylene (PE) separator was interposed between the positive and negative electrodes, and the prepared non-aqueous electrolyte was injected and sealed to prepare a coin cell-type lithium-lithium symmetric cell.
[0127] Examples 3-1 to 3-5 and Comparative Example 3-1: Manufacture of lithium-sulfur battery First, 87.5 parts by weight of a sulfur-carbon (CNT) composite (S / C 75:25 weight ratio) as a positive electrode active material, 5 parts by weight of Denka Black as a conductive material, and 7.5 parts by weight of styrene butadiene rubber / carboxymethyl cellulose (SBR / CMC 7:3) as a binder were mixed to prepare a positive electrode slurry composition, which was then applied to one side of a current collector (Al foil), dried at 80°C, and rolled using a roll press to prepare a positive electrode (at this time, the loading amount was 4.5 mg / cm). 2 (I did.)
[0128] Next, the prepared positive electrode and the lithium metal negative electrode prepared in Examples 1-1 to 1-5 and Comparative Example 1-1 were placed facing each other, and a porous polyethylene (PE) separator was interposed between them. Then, the nonaqueous electrolytes prepared in Examples 2-1 to 2-5 and Comparative Example 2-1 were injected and sealed to prepare a coin cell type lithium-sulfur battery.
[0129] Evaluation example 1: Surface observation of lithium metal anode The surfaces of the lithium metal negative electrode prepared in Example 1-3 and the lithium metal negative electrode prepared in Comparative Example 1-1 were observed by scanning electron microscopy (SEM) and are shown in FIG. 1 and FIG. 2, respectively. In this case, the SEM observation of the lithium metal negative electrode prepared in Example 1-3 was performed immediately after the heat treatment. The SEM equipment used was JEOL JSM-7200F, the magnification was 30,000x, and the acceleration voltage was 5 kV. In addition, the resolution of the equipment used was 1 nm at 20 kV and 1.6 nm at 1 kV, so that at 5 kV it was 1 to 1.6 nm.
[0130] As can be seen from FIG. 2, in the lithium metal anode prepared in Comparative Example 1-1, the surface of the lithium metal was covered with a native oxide layer without any cracks.
[0131] On the other hand, as can be seen from FIG. 1, in the lithium metal negative electrode prepared in Example 1-3, cracks were formed in the oxide layer present on the surface of the lithium metal.
[0132] Evaluation Example 2: Calculation of the area ratio of cracked and non-cracked parts of lithium metal negative electrode The surface area ratio of the cracked portion to the non-cracked portion was calculated using images obtained by observing the surfaces of the lithium metal negative electrodes prepared in Examples 1-1 to 1-5 and Comparative Example 1-1 with an SEM. The SEM equipment used was a JEOL JSM-7200F, the magnification was 30,000x, and the acceleration voltage was 5 kV. The resolution of the equipment used was 1 nm at 20 kV and 1.6 nm at 1 kV, so that the resolution at 5 kV was 1 to 1.6 nm.
[0133] Specifically, in the image observed with the SEM, the non-cracked areas were shown relatively bright because they had a rough surface and protruded, while the cracked areas were shown dark because they had a smooth surface. To utilize this property, the SEM image was binary processed into black and white using 'ImageJ' software, and the colors of the processed image were inverted to maximize the contrast so that the non-cracked areas appeared dark and the cracked areas appeared light. Then, the area ratio was calculated using the areas shown as the cracked and non-cracked areas, and the results are shown in Table 1 below.
[0134] [Table 1]
[0135] Evaluation example 3: Cycle life evaluation of lithium-lithium symmetric cell The lithium-lithium symmetric cells prepared in Examples 2-1 to 2-5 and Comparative Example 2-1 were charged to 1.5 mA / cm at 25° C. 2The cycle life was evaluated by repeating discharge (-1V lower limit) and charge (+1V upper limit) cycles at a current density of 1000 mA, measuring the potential over time (cycle), and the results are shown in Table 2 and Figures 3 to 8 below. When the lithium anode operates smoothly during operation of the symmetric cell, the overvoltage is at the 0.1V level, but as the lithium anode deteriorates, a larger overvoltage is required to desorb lithium. If an overvoltage of -1V is required, it means that lithium is difficult to desorb from the lithium anode, and this may mean that the lithium anode cannot operate normally. Table 2 shows the cell life when the overvoltage required to desorb lithium becomes -1V.
[0136] [Table 2]
[0137] As can be seen from Tables 1, 2 and Figures 3 to 8, the lithium-lithium symmetric cells prepared in Examples 2-1 to 2-5 had cracks formed in the oxide layer on the lithium metal surface, which induced uniform electrodeposition, and thus had improved lifespans compared to the lithium-lithium symmetric cell prepared in Comparative Example 2-1 in which no cracks were formed in the oxide layer on the lithium metal surface. In particular, the lithium-lithium symmetric cells prepared in Examples 2-2 to 2-4, in which the heat treatment temperature was 60°C to 100°C, showed further improved battery lifespans.
[0138] Evaluation example 4: Cycle life evaluation of lithium-sulfur batteries The lithium-sulfur batteries prepared in Examples 3-1 to 3-5 and Comparative Example 3-1 were subjected to 0.2C charge / 0.3C discharge cycles in a voltage range of 1.8V to 2.5V in CC mode at a temperature of 25° C., and the capacity-potential according to the charge-discharge cycles was measured (after a stabilization process of the initial 0.1C / 0.1C 2.5 cycles and 0.2C / 0.2C 3 cycles, the batteries were driven at 0.3C / 0.5C from the 7th cycle). The results are shown in Table 3 and FIG. 9 below.
[0139] [Table 3]
[0140] As can be seen from Table 3 and Figure 9, the lithium-sulfur batteries manufactured in Examples 3-1 to 3-5, which include an oxide layer with cracks formed on the surface of lithium metal, had improved life spans compared to the lithium-sulfur battery manufactured in Comparative Example 3-1, which does not have cracks formed in the oxide layer on the surface of lithium metal. Also, the lithium-sulfur batteries manufactured in Examples 3-2 to 3-4, which have a heat treatment temperature of 60°C to 100°C, were confirmed to have further improved battery life spans. In particular, the lithium-sulfur battery manufactured in Example 3-3, which has a heat treatment temperature in the range of 70°C to 90°C, was confirmed to have a much better life span.
Claims
1. A lithium metal layer; an oxide layer located on at least one surface of the lithium metal layer; A lithium metal negative electrode, wherein the oxide layer has a cracked portion and a non-cracked portion.
2. 2. The lithium metal negative electrode according to claim 1, wherein the area ratio of the cracked portion to the non-cracked portion is 2:8 to 9:
1.
3. 2. The lithium metal negative electrode according to claim 1, wherein the thickness of the oxide layer having the cracks is 50% or less of the maximum thickness of the oxide layer.
4. 2. The lithium metal negative electrode according to claim 1, wherein the oxide layer having the cracks has a thickness of 10 nm to 10 μm.
5. 2. The lithium metal negative electrode of claim 1, wherein the lithium metal layer has a thickness of 1 μm to 200 μm.
6. 1. A method for producing a lithium metal anode comprising: a lithium metal layer; and an oxide layer located on at least one surface of the lithium metal layer, the method comprising: The method of claim 1 , further comprising forming cracks in the oxide layer.
7. The step of forming the crack portion includes:
7. The method of claim 6, further comprising the step of heat-treating the lithium metal negative electrode under a vacuum atmosphere at a pressure of 0.001 to 1 Torr.
8. The step of forming the crack portion includes:
8. The method for producing a lithium metal negative electrode according to claim 6, further comprising the step of heat-treating the lithium metal negative electrode in an inert atmosphere.
9. The step of forming the crack portion includes:
8. The method for preparing a lithium metal negative electrode according to claim 6, further comprising the step of heat-treating the lithium metal negative electrode at a temperature of 40° C. to 120° C.
10. The step of forming the crack portion includes:
8. The method for preparing a lithium metal negative electrode according to claim 6, further comprising the step of heat-treating the lithium metal negative electrode at 65° C. to 85° C.
11. An electrochemical device comprising the lithium metal negative electrode according to any one of claims 1 to 5.
12. 12. The electrochemical device according to claim 11, wherein the electrochemical device comprises a lithium secondary battery.
13. 13. The electrochemical device of claim 12, wherein the lithium secondary battery comprises a lithium ion battery, a lithium sulfur battery, a lithium-lithium symmetric cell, or two or more thereof.
Citation Information
Patent Citations
Negative electrode for coin type lithium secondary battery, its manufacturing method, and coin type lithium secondary battery
JP2007157704A
Protection electrode structure
JP2016511517A
Negative electrode for nonaqueous lithium type power-storage device, and nonaqueous lithium type power-storage device using the same
JP2017135187A
Negative electrode plate, preparation method thereof and electrochemical device
US20200006754A1
Cited By
Negative pole piece, battery and preparation method
CN121862684A
